2017
DOI: 10.1080/08037051.2017.1306422
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age on left ventricular geometry and diastolic function in elderly patients with treated hypertension

Abstract: Age was independently correlated with LV concentric/functional changes regardless of LV hypertrophy, suggesting that ageing is independently involved in the progression of LV remodelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
9
1
Order By: Relevance
“…One of the reasons for such a large difference in cLVH prevalence may be aging. In general, older age is strongly correlated with LVH [17,18]. Although the mean age of patients was 42 years in the previous study that showed a lower prevalence of cLVH, it was 60.8 years in our study [16].…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…One of the reasons for such a large difference in cLVH prevalence may be aging. In general, older age is strongly correlated with LVH [17,18]. Although the mean age of patients was 42 years in the previous study that showed a lower prevalence of cLVH, it was 60.8 years in our study [16].…”
Section: Discussioncontrasting
confidence: 63%
“…The associations were not observed in elderly patients. Previous reports have shown that age is independently associated with LV concentric change [17,18] and recent basic studies have reported that several cellular and molecular changes, such as reduction of cardiomyocytes, replacement hypertrophy of residual cardiomyocytes, deposition of extracellular matrix, and extracellular fibrosis were observed in LV with aging [20,21]. These histological changes may lead LVs to undergo undesirable morphological changes, such as LVH.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have suggested a relationship between orthostatic hypotension and frailty, but there are no consistent results . Recently, we reported that aging itself increased left ventricular relative wall thickness independent of systolic BP level in hypertensive outpatients, and that subclinical orthostatic hypotension was attributable to decreased stroke volume, due to increased relative wall thickness and to arterial elasticity, measured as stroke volume per pulse pressure ratio, rather than autonomic nerve dysfunction . Orthostatic BP change and arterial stiffness measured by carotid‐femoral pulse wave velocity were also reported to be related …”
Section: Introductionmentioning
confidence: 82%
“…Previous research found that 10% of hypertension could cause a cardiac diastolic function decline [ 17 , 18 ]. Long-term hypertension, especially poorly controlled, could decrease the left ventricular compliance and increase stiffness [ 19 21 ]. AF could cause a variety of hemodynamic abnormalities such as rapid and irregular atrial activation impairing atrial contractile function, loss of regularity of atrioventricular conduction, and irregular ventricular contraction.…”
Section: Discussionmentioning
confidence: 99%